Exploring the neutral invertase–oxidative stress defence connection in Arabidopsis thaliana - Xiang, Li (Oxford University Press, 2011)
Over the past decades, considerable advances have been made in understanding the crucial role and the regulation of sucrose metabolism in plants. Among the various sucrose-catabolizing enzymes, alkaline/neutral invertases (A/N-Invs) have long remained poorly studied. However, recent findings have demonstrated the presence of A/N-Invs in various organelles in addition to the cytosol, and their importance for plant development and stress tolerance. A cytosolic (At-A/N-InvG, At1g35580) and a mitochondrial (At-A/N-InvA, At1g56560) member of the A/N-Invs have been analysed in more detail in Arabidopsis and it was found that At-A/N-InvA knockout plants show an even more severe growth phenotype than At-A/N-InvG knockout plants. The absence of either A/N-Inv was associated with higher oxidative stress defence gene expression, while transient overexpression of At-A/N-InvA and At-A/N-InvG in leaf mesophyll protoplasts down-regulated the oxidative stress-responsive ascorbate peroxidase 2 (APX2) promoter. Moreover, up-regulation of the APX2 promoter by hydrogen peroxide or abscisic acid could be blocked by adding metabolizable sugars or ascorbate. A hypothetical model is proposed in which both mitochondrial and cytosolic A/N-Invs can generate glucose as a substrate for mitochondria-associated hexokinase, contributing to mitochondrial reactive oxygen species homeostasis.